A note on promoting positive emergence and managing negative emergence in systems of systems. (January 2016) - Zeigler, Bernard P
"Emergence" is a descriptive term that is gaining currency for a set of phenomena that are becoming increasingly important to understand scientifically. Recently, several works have used the context of socio-technical systems of systems to serve as a germane abstraction for characterizing emergence. In this note, we formulate conditions as a tri-layer architecture required for promoting the emergence of desired behaviors in a system of systems and managing unintended undesired effects.